Migration and identity processes of Slovenians in Argentina - Molek, Nadia (Dve domovini, 2025)
This review analyzes and compares scholarship on Slovenian migration to Argentina, highlighting disparities between Slovenian and Argentine academic approaches. While Slovenian researchers have examined identity, politics, and transnational ties in-depth, Argentine contributions are limited. The study includes works by migrants and descendants, showing how community narratives shape collective memory. It concludes that the literature is rich but marked by national biases, calling for more interdisciplinary, integrative research.
Keywords: identity processes; migracijski procesi; migration processes; narativni pregled literature; narrative literature review; procesi identitete; Slovenian migrants; slovenski izseljenci